A novel model of colitis-associated cancer in SAMP1/YitFc mice with Crohn's disease-like ileitis. - Paola Menghini; Luca Di Martino; Loris R Lopetuso; Daniele Corridoni; Joshua C Webster; Wei Xin; Kristen O Arseneau; Minh Lam; Theresa T Pizarro; Fabio Cominelli (PLoS ONE, 2017)
Patients with inflammatory bowel disease (IBD) are at increased risk for developing colorectal cancer. Evidence suggests that colonic dysplasia and colitis-associated cancer (CAC) are often linked to repeated cycles of epithelial cell injury and repair in the context of chronic production of inflammatory cytokines. Several mouse models of CAC have been proposed, including chemical induction through exposure to dextran sulfate sodium (DSS) with the genotoxic agents azoxymethane (AOM), 1,2-dymethylhydrazine (DHM) or targeted genetic mutations. However, such models are usually performed on healthy animals that usually lack the underlying genetic predisposition, immunological dysfunction and dysbiosis characteristic of IBD. We have previously shown that inbred SAMP1/YitFc (SAMP) mice develop a progressive Crohn's disease (CD)-like ileitis in the absence of spontaneous colitis. We hypothesize that SAMP mice may be more susceptible to colonic tumorigenesis due to their predisposition to IBD. To test this hypothesis, we administered AOM/DSS to IBD-prone SAMP and their non-inflamed parental control strain, AKR mice. Our results showed that AOM/DSS treatment enhanced the susceptibility of colitis in SAMP compared to AKR mice, as assessed by endoscopic and histologic inflammatory scores, daily weight loss and disease activity index (DAI), during and after DSS administration. SAMP mice also showed increased colonic tumorigenesis, resulting in the occurrence of intramucosal carcinoma and a higher incidence of high-grade dysplasia and tumor burden. These phenomena occurred even in the absence of AOM and only upon repeated cycles of DSS. Taken together, our data demonstrate a heightened susceptibility to colonic inflammation and tumorigenesis in AOM/DSS-treated SAMP mice with CD-like ileitis. This novel model represents a useful tool to investigate relevant mechanisms of CAC, as well as for pre-clinical testing of potential IBD and colon cancer therapeutics.